Ionic screening and dissociation are crucial for understanding chemical self-propulsion in polar solvents. Issue 6 (18th January 2017) - Brown, Aidan T.; Poon, Wilson C. K.; Holm, Christian; de Graaf, Joost
Abstract : The ionic dissociation of polar solvents such as water and hydrogen peroxide significantly modifies the predicted speed and behavior of chemically propelled microswimmers. Abstract : Polar solvents like water support the bulk dissociation of themselves and their solutes into ions, and the re-association of these ions into neutral molecules in a dynamic equilibrium, e.g., H2 O2 ⇌ H + + HO2 − . Using continuum theory, we study the influence of these association–dissociation reactions on the self-propulsion of colloids driven by surface chemical reactions (chemical swimmers). We find that association–dissociation reactions should have a strong influence on swimmers' behaviour, and therefore should be included in future modelling. In particular, such bulk reactions should permit charged swimmers to propel electrophoretically even if all species involved in the surface reactions are neutral. The bulk reactions also significantly modify the predicted speed of chemical swimmers propelled by ionic currents, by up to an order of magnitude. For swimmers whose surface reactions produce both anions and cations (ionic self-diffusiophoresis), the bulk reactions produce an additional reactive screening length, analogous to the Debye length in electrostatics. This in turn leads to an inverse relationship between swimmer radius and swimming speed, which could provide an alternative explanation for recent experimental observations on Pt-polystyrene Janus swimmers [S. Ebbens et al., Phys. Rev. E: Stat., Nonlinear, Soft Matter Phys., 2012, 85, 020401]. We also use our continuum theory to investigate the effect of the Debye screening length itself, going beyond the infinitely-thin-screening-length approximation used by previous analytical theories. We identify significant departures from this limiting behaviour for micron-sized swimmers under typical experimental conditions and find that the approximation fails entirely for nanoscale swimmers.